Pentingnya Indikator Satuan Epidmiolog Dalam Rangka Kebijakan Pada Pencegahan Kejadian Stunting - Sutarto Sutarto; Reni Indriyani (Nutrition Department, Poltekkes Kemenkes Tanjung Karang, 2025)
Stunting is a global health problem that has a significant impact on the quality of human resources in the future, especially in Indonesia. Although various policies have been implemented to reduce the prevalence of stunting, the stunting rate is still high, indicating the need for further evaluation of the effectiveness of these policies. This article discusses the importance of using epidemiological unit indicators, such as stunting prevalence, infant mortality rate, immunization coverage, and sanitation, in monitoring and designing more effective stunting prevention policies. These indicators provide a clearer picture of the factors that influence the success of the policy, as well as support data-based decision-making. In addition, health education also plays an important role in stunting prevention efforts, especially through ongoing outreach programs for the community, especially pregnant and breastfeeding mothers. Effective outreach programs can raise awareness of the importance of balanced nutrition and good parenting during the First 1000 Days of Life. Through a multisectoral approach involving the health, education, and social sectors, as well as strengthening the role of health cadres, it is hoped that the prevalence of stunting can decrease significantly. This article also recommends the use of technology to expand the reach of health education and conduct regular policy evaluations to adjust to findings in the field.